Altered faecal microbiome and metabolome in IgG4-related sclerosing cholangitis and primary sclerosing cholangitis. Issue 5 (25th May 2021) - Liu, Qiaoyan; Li, Bo; Li, Yikang; Wei, Yiran; Huang, Bingyuan; Liang, Jubo; You, Zhengrui; Li, You; Qian, Qiwei; Wang, Rui; Zhang, Jun; Chen, Ruiling; et al.
Abstract : Objective: Multiple clinical similarities exist between IgG4-related sclerosing cholangitis (IgG4-SC) and primary sclerosing cholangitis (PSC), and while gut dysbiosis has been extensively studied in PSC, the role of the gut microbiota in IgG4-SC remains unknown. Herein, we aimed to evaluate alterations of the gut microbiome and metabolome in IgG4-SC and PSC. Design: We performed 16S rRNA gene amplicon sequencing of faecal samples from 135 subjects with IgG4-SC (n=34), PSC (n=37) and healthy controls (n=64). A subset of the samples (31 IgG4-SC, 37 PSC and 45 controls) also underwent untargeted metabolomic profiling. Results: Compared with controls, reduced alpha-diversity and shifted microbial community were observed in IgG4-SC and PSC. These changes were accompanied by differences in stool metabolomes. Importantly, despite some common variations in the microbiota composition and metabolic activity, integrative analyses identified distinct host–microbe associations in IgG4-SC and PSC. The disease-associated genera and metabolites tended to associate with the transaminases in IgG4-SC. Notable depletion of Blautia and elevated succinic acid may underlie hepatic inflammation in IgG4-SC. In comparison, potential links between the microbial or metabolic signatures and cholestatic parameters were detected in PSC. Particularly, concordant decrease of Eubacterium and microbiota-derived metabolites, including secondary bile acids, implicated novel host–microbial metabolic pathways involving cholestasis of PSC. Interestingly, the predictive models based on metabolites were more effective in discriminating disease status than those based on microbes. Conclusions: Our data reveal that IgG4-SC and PSC possess divergent host–microbe interplays that may be involved in disease pathogenesis. These data emphasise the uniqueness of IgG4-SC.